DEVELOPMENT OF A PROTOTYPE DATABASE OF INFORMATION TECHNOLOGY FOR MONITORING WATER CONSUMPTION FROM THE WATER SUPPLY NETWORK OF SETTLEMENTS - DAVYDENKO, NINA; KUNYTSKYI, SERGII (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The availability of reliable and systematic information on water consumption modes is the basis for optimizing the operation modes of water supply facilities. The necessity of water consumption monitoring is substantiated in order to detect changes in the operation conditions of water supply system facilities due to the influence of seasonal and social factors. The daily water consumption graph was used as an indicator of the operation mode of water supply facilities. The procedure of analysis of actual water consumption graphs is the methodological basis of the proposed information technology. It involves the search for hidden regularities in the formation of water consumption and is based on the description of irregularities and the form of daily water consumption graphs. The design of the information technology prototype is performed using a unified modeling language. The functionality and behavior of information monitoring technology is described using a use case diagram. A structured database is the information basis of information technology. It contains a structured set of initial data on daily water consumption graphs, the results of the description of their irregularities and shapes, the results of the classification of daily water consumption graphs and a formalized description of the analysis results. A relational data model was used to construct the database. The developed database contains twelve tables. Relationship between tables is defined as «one to many». Implementation of monitoring on a regular basis will ensure the accumulation of new data. The integration of the developed prototype database and information technology into the information system for monitoring the functioning of the water supply system will help to identify new knowledge about the peculiarities of the formation of the water consumption mode. This will identify changes in the actual operation conditions of water supply facilities.